Phytoremediation for heavy metal‐contaminated soils combined with bioenergy production - Ginneken, Luc Van; Meers, Erik; Guisson, Ruben; Ruttens, Ann; Elst, Kathy; Tack, Filip M. G.; Vangronsveld, Jaco; Diels, Ludo; Dejonghe, Winnie (Journal of Environmental Engineering and Landscape Management, 2007)
In June 2007, a project started in Flanders (Belgium) in which we will apply phytoremediation to clean soils that are diffusely polluted with heavy metals. Uptake ranges of heavy metals by rape seed, maize and wheat will be enhanced by increasing the bioavailability of these heavy metals by the addition of biodegradable physico‐chemical agents and by stimulating the heavy‐metal uptake capacity of the microbial community in and around the plant. In addition, the harvested biomass crops will be converted into bioenergy by using different energy‐recovery‐techniques. The energy and heavy metal mass balances will be compared for four different energy‐recovery techniques (anaerobic digestion, incineration, gasification and production of biodiesel). The overall information obtained will result in an economic evaluation of the use of phytoremediation combined with bioenergy production for the remediation of sites which are diffusely polluted with heavy metals. In the present review we will first explain the most important research steps investigated in our phytoremediation project. Secondly, an overview of literature discussing the phytoremediation capacity of rape seed to clean soils that are contaminated with heavy metals and the possibilities to produce biodiesel from this (heavy metal polluted) rape seed will be discussed in more detail. Fitoremediacijos taikymas sunkiaisiais metalais užterštame dirvožemyje derinant su bioenergijos gamyba Santrauka. 2007 m. birželį Flandrijoje (Belgija) pradėtas vykdyti projektas, kuriame mes pritaikysime fitoremediaciją siekdami išvalyti sunkiuosius metalus iš dirvožemio. Sunkiųjų metalų patekimas į rapsus, kukurūzus ir kviečius bus suintensyvintas didinant šių sunkiųjų metalų biopriimamumą dėl pridedamų biodegraduojančių fizikinių-cheminių priedų bei stimuliuojant mikrobiologinių bendrijų pajėgumą augale ir aplink jį sugerti sunkiuosius metalus. Be to, nuimta javų biomasė bus perdirbta į bioenergiją, taikant įvairias energijos gavybos technologijas. Energijos ir sunkiųjų metalų masės balansas bus palygintas pagal keturias skirtingas energijos gavybos technologijas (anaerobinis kompostavimas, deginimas, dujofikavimas ir biodyzelio gamyba). Visa gauta informacija leis ekonominiu požiūriu įvertinti fitoremediacijos, derinamos su bioenergijos gamyba, taikymą valant sunkiaisiais metalais nevienodai užterštus plotus. Pateikiamoje apžvalgoje pirma aptarsime svarbiausius fitoremediacijos projekto etapus. Antra, detaliau apžvelgsime literatūrą apie rapsų pajėgumą išvalyti dirvožemį, užterštą sunkiaisiais metalais, ir galimybes gaminti biodyzelį iš (sunkiaisiais metalais užterštų) rapsų sėklų. Reikšminiai žodžiai: fitoremediacija, sunkieji metalai, biomasė, energijos gamyba, rapsai, biodyzelis. Применение фиторемедиации в почве, загрязненной тяжелыми металлами и приспосабливаемой для производства биоэнергии Резюме. В июне 2007 г. во Фландере (Бельгия) была начата работа над проектом по фиторемедиации с целью очищения почвы от тяжелых металлов. Процесс поглощения тяжелых металлов рапсом, кукурузой и пшеницей будет более интенсивным благодаря введению биодеградирующих физико-химических добавок и стимуляции способности микробиологических сообществ в растении и вокруг него впитывать тяжелые металлы. Снятая биомасса зерновых с помощью различных технологий по производству энергии будет конвертирована в биоэнергию. Баланс энергии и массы тяжелых металлов будет сравнен с помощью четырех разных технологий по производству энергии (анаэробического компостирования, сжигания, газофикации, производства биотоплива). Полученная информация позволит с экономической точки зрения оценить применение фиторемедиации как для очищения площадей, в разной степени загрязненных тяжелыми металлами, так и для производства биоэнергии. В статье прежде всего проанализированы важнейшие этапы проекта по фиторемедиации. Затем произведен обзор литературы о способности рапса благодаря фиторемедиации очищать почву, загрязненную тяжелыми металлами, и возможностях производства биотоплива из семян рапса, загрязненных тяжелыми металлами. Ключевые слова: фиторемедиация, тяжелые металлы, биомасса, производство энергии, семена рапса, биотопливо. First Published Online: 14 Oct 2010